Pengelolaan Media Sosial Peace Generation Indonesia Dalam Mengampanyekan Nilai-Nilai Perdamaian - Aat Ruchiat Nugraha Nugraha (LPPM Stikosa - AWS, 2020)
Technological advances are rapidly causing a change in a variety of ways, especially increasing the rapid use of the Internet that can utilize to abuse in the